First observation of the cosmic ray shadow of the Moon and the Sun with KM3NeT/ORCA - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; M. Anghinolfi; M. Anguita; M. Ardid; S. Ardid; J. Aublin; et al. (The European Physical Journal C, 2023)
This article reports the first observation of the Moon and the Sun shadows in the sky distribution of cosmic-ray induced muons measured by the KM3NeT/ORCA detector. The analysed data-taking period spans from February 2020 to November 2021, when the detector had 6 Detection Units deployed at the bottom of the Mediterranean Sea, each composed of 18 Digital Optical Modules. The shadows induced by the Moon and the Sun were detected at their nominal position with a statistical significance of 4.2 sigma and 6.2 sigma, and an angular resolution of sigma_res = 0.49^o and sigma_res = 0.66^o , respectively, consistent with the prediction of from simulations. This early result confirms the effectiveness of the detector calibration, in time, position and orientation and the accuracy of the event direction reconstruction. This also demonstrates the performance and the competitiveness of the detector in terms of pointing accuracy and angular resolution.